The effect of textual variation on concept based information retrieval. - Aronson, A. R. (American Medical Informatics Association, 1996)
Accounting for textual variation in the documents and queries processed by information retrieval systems is considered essential for achieving good retrieval. Recent research has called into question several of the techniques used to support this endeavor. This paper reports on experiments with a concept based information retrieval system which relies on a program called MetaMap to account for textual variation in the process of mapping biomedical text such as MEDLINE bibliographic citations to the UMLS Metathesaurus. The experiments confirm that the effort expended in handling textual variation is well-spent for at least one type of concept based information retrieval.